1986
DOI: 10.1099/0022-1317-67-5-907
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus RNA Detected in Paget's Disease Bone Tissue by in situ Hybridization

Abstract: SUMMARYMorphological and immunocytological studies have demonstrated the presence of paramyxovirus antigens in Paget's bone disease tissue and in particular antigens related to measles virus and respiratory syncytial virus. To examine the relationship between measles virus and Paget's bone disease we used in situ hybridization and a cloned measles virus DNA probe specific for the nucleocapsid protein to detect and locate measles virus RNA sequences in Paget's bone tissue. In five patients with the disease, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…(9) Subsequently, antisera against measles virus and respiratory syncitial virus were applied to both pagetic osteoclasts (21) and pagetic marrow cells from long-term cultures (22) ; in each case, viral antigens were expressed. In situ hybridization techniques have demonstrated evidence of both measles virus (23) and canine distemper virus (10,24) in pagetic bone, and measles virus nucleocapsid transcripts can be detected in pagetic bone marrow mononuclear cells. (25,26) However, many of these observations have been questioned, (27,28) and a viral etiology for Paget's disease has not been confirmed.…”
Section: Epidemiology Of Paget's Diseasementioning
confidence: 99%
“…(9) Subsequently, antisera against measles virus and respiratory syncitial virus were applied to both pagetic osteoclasts (21) and pagetic marrow cells from long-term cultures (22) ; in each case, viral antigens were expressed. In situ hybridization techniques have demonstrated evidence of both measles virus (23) and canine distemper virus (10,24) in pagetic bone, and measles virus nucleocapsid transcripts can be detected in pagetic bone marrow mononuclear cells. (25,26) However, many of these observations have been questioned, (27,28) and a viral etiology for Paget's disease has not been confirmed.…”
Section: Epidemiology Of Paget's Diseasementioning
confidence: 99%
“…Although the exact etiology of Paget disease is unknown, previous studies suggested that genetic and environmental factors may play a role in the pathogenesis 1617. Viral infection has been suggested to play a pathogenetic role 1618. Particles resembling those of paramyxovirus and nucleic acid sequences of measles virus, respiratory syncytial virus and canine distemper virus have all been reported from pagetic bones.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclei do not harbor the inclusions seen in osteoclasts, although evidence of measles virus nucleocapsid transcripts has been found in osteoblasts as determined by in situ hybridization. (30) The cells are otherwise indistinguishable from osteoblasts found in normal bone. (38) …”
Section: Osteoblastsmentioning
confidence: 99%
“…They were judged to represent defective viruses because (with the exception of two cases in one report) budding of intact virions from cell surfaces was not observed. (9) Further support for a viral origin of the inclusions has come from immunostaining of the cells with monoclonal antibodies to measles virus and respiratory syncytial virus, (29) from demonstration of measles virus RNA in pagetic bone by in situ hybridization, (30) from demonstration of measles virus nucleocapsid transcripts by reverse transcriptase and PCR in pagetic bone marrow cells and circulating mononuclear cells, (31) from demonstration of measles virus nucleocapsid sequences in pagetic bone marrow cells, (32) and from the observation that RNase removes the microtubular nuclear and cytoplasmic inclusions from pagetic bone. (10) Canine distemper virus RNA has also been found in the bone from Paget's disease patients in England.…”
Section: Osteoclastsmentioning
confidence: 99%